2022
DOI: 10.3390/metabo12010035
|View full text |Cite
|
Sign up to set email alerts
|

Mining for Active Molecules in Probiotic Supernatant by Combining Non-Targeted Metabolomics and Immunoregulation Testing

Abstract: Chronic respiratory diseases such as asthma are highly prevalent in industrialized countries. As cases are expected to rise, there is a growing demand for alternative therapies. Our recent research on the potential benefits of probiotics suggests that they could prevent and reduce the symptoms of many diseases by modulating the host immune system with secreted metabolites. This article presents the first steps of the research that led us to identify the immunoregulatory bioactivity of the amino acid d-Trp repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…As reported, 3‐HAA possesses immune‐modulatory properties per se and strong antioxidant activities. [ 54 ] It can induce lymphocyte apoptosis and T cell suppression by inhibiting the NF‐ κ B signaling pathway, thereby decreasing the levels of proinflammatory cytokines (e.g., TNF‐ α and IL‐6). [ 55 ] Another study revealed that its anti‐inflammatory mechanism was associated with an increase in the level of Foxp3 + regulatory T cells.…”
Section: Resultsmentioning
confidence: 99%
“…As reported, 3‐HAA possesses immune‐modulatory properties per se and strong antioxidant activities. [ 54 ] It can induce lymphocyte apoptosis and T cell suppression by inhibiting the NF‐ κ B signaling pathway, thereby decreasing the levels of proinflammatory cytokines (e.g., TNF‐ α and IL‐6). [ 55 ] Another study revealed that its anti‐inflammatory mechanism was associated with an increase in the level of Foxp3 + regulatory T cells.…”
Section: Resultsmentioning
confidence: 99%
“…We previously described bioactivity-guided chromatography combined with ultrahigh-resolution mass spectrometry for the discovery of novel bioactive compounds ( 14 , 15 ). Here, the dried bioactive and inactive chromatographic fractions were solubilized in minimal volume of water (200 µl) diluted in methanol 1:5 (v:v) for direct injection at 2 µl/min into electrospray ionization negative mode ultrahigh-resolution mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…Gut microbial metabolites such as SCFAs, amino acids, bile acids, and vitamins involved in immune regulation are modulated by probiotics and influence the outcome of intestinal inflammation. SCFAs exert anti-inflammatory effects by binding to specific receptors on epithelial cells, inhibiting the production of pro-inflammatory cytokines [ 57 ]. Probiotic metabolites such as amino acids and amino acid derivatives interact with immune cell surface receptors and exert anti-inflammatory effects [ 57 ].…”
Section: Immunoregulatory Effects Of Probioticsmentioning
confidence: 99%
“…SCFAs exert anti-inflammatory effects by binding to specific receptors on epithelial cells, inhibiting the production of pro-inflammatory cytokines [ 57 ]. Probiotic metabolites such as amino acids and amino acid derivatives interact with immune cell surface receptors and exert anti-inflammatory effects [ 57 ]. An interesting effect of probiotics is their metabolization of primary bile acids to secondary bile acids which bind to various GPCR—G-protein coupled receptors or nuclear receptors to control mucosal immune activity and decrease inflammation [ 58 ].…”
Section: Immunoregulatory Effects Of Probioticsmentioning
confidence: 99%